Audit of Surgical practice and performance in COVID Crisis – Lessons for the future - Anum Arif, Alishba Kulsoom Rauf, Fatima Kharal, Ahsin Manzoor Bhatti, Muhammad Salman Imtiaz, Raoon, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the pattern of surgical emergencies and surgical care provided during COIVD 19 pandemic. Study design: Cross-sectional Study Place and duration of study: Department of Surgery, CMH, Lahore from 15th March - 15 June 2020. Methodology: Data was collected retrospectively, of all the patients who were admitted in department of surgery over the duration of 3 months. Demographic variables, diagnosis, work up related to COVID-19, specialty of admission and surgical vs conservative management was recorded. Results: A total of 312 patients were included. Majority were male 216(69.2%). Most of the patients 191(61.2%) were admitted via clinic, predominantly in month of May 148(41%). COVID-19 PCR was done on 210 patients (67.3%), chest x-ray was done on 271(87.9%), HRCT chest was done on 113 patients (29.20%). Although general surgery was the busiest service line with a total patient admission of 89(43.1%), Orthopedic surgery top the operative interventions list with 85.1% of admissions underwent operative management. Conclusion: The current local guidelines about patient flow and management of patients in COVID crisis are practical and can be implemented. In the wake of the later waves of COVID 19 hospitals should prepare to divert their resources to high volume specialties like General and orthopedic surgery. Simple, but important procedures like arteriovenous fistula creation should only be stopped it there is shortage of manpower. MeSH words: Audit, COVID- 19, General Surgery, Pakistan, Vascular Surgery